Correcção de uma má-oclusão de Classe II divisão 1 em duas fases de tratamento - Ponces, MJ (2007)
The influence of functional appliances on craniofacial growth as well as the two-phase orthodontic treatment philosophy are still controversial subjects. The main purpose of the two-phase treatment involving activators is to promote dento-alveolar changes. The goal of the second phase is creating an occlusion according to functional occlusion patterns. The aim of this article is to present the sequence of a Class II Division 1 treatment case in two phases, in which a Teuscher activator is used in the first phase.